Myriophyllum rubricaule sp. nov., a M. aquaticum look-alike only known in cultivation - Van Valkenburg, Johan L.C.H.; Duistermaat, Leni (H.); Boer, Edu; Raaymakers, Tom M. (European Journal of Taxonomy, 2022)
A confusingly labeled water-milfoil of obscure status, known only in cultivation, is here formally described as a new species, Myriophyllum rubricaule Valk. & Duist. sp. nov. This species has fully replaced M. aquaticum in the horticultural trade in Europe since the addition of M. aquaticum to the list of invasive alien species of Union concern (EU regulation no. 1143/2014) in 2016. This manuscript provides a morphological description of M. rubricaule sp. nov., and its distinction from M. aquaticum is further supported by molecular data (chloroplast and nuclear loci).